Solve for y g=(2y-m)/y

Math
g=2y-my
Rewrite the equation as 2y-my=g.
2y-my=g
Solve for y.
Tap for more steps…
Multiply each term by y and simplify.
Tap for more steps…
Multiply each term in 2y-my=g by y.
2y-my⋅y=g⋅y
Cancel the common factor of y.
Tap for more steps…
Cancel the common factor.
2y-my⋅y=g⋅y
Rewrite the expression.
2y-m=g⋅y
2y-m=gy
2y-m=gy
Subtract gy from both sides of the equation.
2y-m-gy=0
Add m to both sides of the equation.
2y-gy=m
Factor y out of 2y-gy.
Tap for more steps…
Factor y out of 2y.
y⋅2-gy=m
Factor y out of -gy.
y⋅2+y(-g)=m
Factor y out of y⋅2+y(-g).
y(2-g)=m
y(2-g)=m
Divide each term by 2-g and simplify.
Tap for more steps…
Divide each term in y(2-g)=m by 2-g.
y(2-g)2-g=m2-g
Cancel the common factor of 2-g.
Tap for more steps…
Cancel the common factor.
y(2-g)2-g=m2-g
Divide y by 1.
y=m2-g
y=m2-g
y=m2-g
y=m2-g
Solve for y g=(2y-m)/y

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top